Prevalence and correlates of tobacco use in bipolar disorder: data from the first 2000 participants in the Systematic Treatment Enhancement Program. - Waxmonsky, J; Thomas, MR; Miklowitz, D; Allen, M; Wisniewski, SR; Zhang, H; Ostacher, M; Fossey, MD (2005)
OBJECTIVE: Only a few small descriptive studies have examined the prevalence and correlates of tobacco use among bipolar patients. We predicted that poorly controlled manic, depressed and mixed states, and the presence of psychotic symptoms, would be associated with a greater prevalence of smoking among patients with bipolar disorder. METHOD: We examined the prevalence of smoking in a cross-sectional sample of 1904 patients with bipolar disorder enrolled in the National Institute of Mental Health's Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) database. We also examined the relationship between smoking and other factors including: bipolar subtype, current clinical status, illness severity (e.g., number of prior mood episodes), age of bipolar onset, gender, education, socioeconomic status, and concurrent substance use. RESULTS: At STEP-BD program entry, 31.2% of patients reported that they were smokers. Patients who were male, less educated, and/or had lower income were more likely to be smokers (P<.01). Additionally, patients with rapid cycling, comorbid psychiatric disorders, and/or substance abuse, and those experiencing a current episode of illness were more likely to be smokers (P<.0001). More lifetime depressive and manic episodes as well as greater severity of depressive and manic symptoms were associated with smoking (P<.001). Use of atypical antipsychotic medications was more prevalent among smokers (P=.04). CONCLUSIONS: Clinical and demographic variables are associated with smoking in this sample of bipolar patients. Longitudinal analyses are needed to determine how mood and bipolar symptoms interact with smoking over the episodic course of bipolar disorder. Additional studies should focus on whether controlling bipolar symptoms is associated with cessation of smoking.